KONTRIBUSI UMAYYAH ANDALUSIA DALAM PENGEMBANGAN ILMU PENGETAHUAN - J, Irwan Supriadin (STIT Sunan Giri Bima, 2020)
The Andalusian Umayyad dynasty was a continuation of the Damascus Umayyad which was destroyed on the Iberian peninsula, the entry of Islam in Andalusia was first brought by the commander Tharif bin Malik at the suggestion of Musa bin Nushair to the Caliph al-Walid. After conquering Christian kingdoms in almost all regions of Andalusia, the rulers of the Umayyad dynasty focused their attention on the development of science and science which made big names like Ibn Rushd, Ibn Firnas and Ibn Hazm. The Andalusian rulers opened the palace doors as wide as possible for discussion activities, provided laboratories and made the palace a gathering place for art experts and writers from all over to pour works and artistic creations. The government's attention to scientists made Andalusia a beacon of civilization at a time when European society lived in darkness and ignorance. The progress that was made during the Umayyad Andalusian era which would later inspire the birth of the Renaissance era which was marked by the industrial revolution in Europe.